Treatise on Sociological Jurisprudence: Oriental and Occidental Perspective - Sapkota, Sujit; Katuwal, Shiddhartha (KDCBAR Law Journal, 2025)
Jurisprudence is an ocean of legal philosophy or thought which depth can never be discovered. The formal categorization of jurisprudential ideas in forms of six schools of thought is merely an attempt to a systematic jurisprudential study. In this regard, this paper tries to examine the philosophy or notion of one of those schools of thoughts i.e Sociological school of thoughts from multi-dimensional perspective particularly perceiving it from the lens of oriental and occidental society. In our jurisprudential schooling of any levels, we are rarely informed about the oriental jurisprudential development particularly while being taught about six schools of thoughts which are foundational stone of jurisprudence. The occidental sociological jurisprudence is indeed systematized and it has formal development in particular framework of time but saying this we can’t overlook the oriental sociological jurisprudence which developed in our soil, civilization in various point of time. Occidental sociological jurisprudence can be easily traced out from any jurisprudential writing but tracing out oriental jurisprudence isn’t as easy as that. The paper aims to introduce the uninformed oriental sociological jurisprudence along with examination of development of occidental sociological jurisprudence along with their contributors also with special reference to Nepalese sociological jurisprudential development with constructive role played by judiciary in its development.